Cost‐effectiveness of noninvasive liver fibrosis tests for treatment decisions in patients with chronic hepatitis C. Issue 3 (29th July 2014) - Tsochatzis, Emmanuel A.; Crossan, Catriona; Longworth, Louise; Gurusamy, Kurinchi; Rodriguez‐Peralvarez, Manolo; Mantzoukis, Konstantinos; O'Brien, Julia; Thalassinos, Evangelos; Papastergiou, Vassilios; Noel‐Storr, Anna; Davidson, Brian; Burroughs, Andrew K.
<x xml:space="preserve">Abstract</x> The cost‐effectiveness of noninvasive tests (NITs) as alternatives to liver biopsy is unknown. We compared the cost‐effectiveness of using NITs to inform treatment decisions in adult patients with chronic hepatitis C (CHC). We conducted a systematic review and meta‐analysis to calculate the diagnostic accuracy of various NITs using a bivariate random‐effects model. We constructed a probabilistic decision analytical model to estimate health care costs and outcomes (quality‐adjusted life‐years; QALYs) using data from the meta‐analysis, literature, and national UK data. We compared the cost‐effectiveness of four treatment strategies: testing with NITs and treating patients with fibrosis stage ≥F2; testing with liver biopsy and treating patients with ≥F2; treat none; and treat all irrespective of fibrosis. We compared all NITs and tested the cost‐effectiveness using current triple therapy with boceprevir or telaprevir, but also modeled new, more‐potent antivirals. Treating all patients without any previous NIT was the most effective strategy and had an incremental cost‐effectiveness ratio (ICER) of £9, 204 per additional QALY gained. The exploratory analysis of currently licensed sofosbuvir treatment regimens found that treat all was cost‐effective, compared to using an NIT to decide on treatment, with an ICER of £16, 028 per QALY gained. The exploratory analysis to assess the possible effect on results of new treatments, found that if SVR rates increased to >90% for genotypes 1‐4, the incremental treatment cost threshold for the "treat all" strategy to remain the most cost‐effective strategy would be £37, 500. Above this threshold, the most cost‐effective option would be noninvasive testing with magnetic resonance elastography (ICER = £9, 189). Conclusions: Treating all adult patients with CHC, irrespective of fibrosis stage, is the most cost‐effective strategy with currently available drugs in developed countries. (Hepatology 2014;60:832–843)